Sleep as a Mediator in the Pathway Linking Environmental Factors to Hypertension: A Review of the Literature - Oluwaseun A. Akinseye; Stephen K. Williams; Azizi Seixas; Seithikurippu R. Pandi-Perumal; Julian Vallon; Ferdinand Zizi; Girardin Jean-Louis (International Journal of Hypertension)
Environmental factors, such as noise exposure and air pollution, are associated with hypertension. These environmental factors also affect sleep quality. Given the growing evidence linking sleep quality with hypertension, the purpose of this review is to investigate the role of sleep as a key mediator in the association between hypertension and environmental factors. Through this narrative review of the extant literature, we highlight that poor sleep quality mediates the relationship between environmental factors and hypertension. The conceptual model proposed in this review offers opportunities to address healthcare disparities in hypertension among African Americans by highlighting the disparate impact that the predictors (environmental factors) and mediator (sleep) have on the African-American community. Understanding the impact of these factors is crucial since the main outcome variable (hypertension) severely burdens the African-American community.